1981
DOI: 10.1017/s1742758400000953
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens of veterinary importance isolated from mosquitoes and biting midges in Israel

Abstract: In a bluetongue (BT) disease project, light trappings of Culkoides were conducted in 19 localities and 39,000 biting midges were examined. BT virus type 16 was isolated in 1968 at Devora from a pool consisting mainly of Culicoides schultzei gp and C. imicola; BT virus type 4 was isolated in 1969 at Yesodot from a pool of 183 C. imicola; BT virus type 2 was isolated in 1979 at Talme El'azar from pools consisting of 2462 C. imicola; and BT virus type 6 was isolated 3 times in 1980 at Bet Dagan from pools of 204,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Vector competence studies for these arboviruses are most complete for AKAV, particularly in Australia where the role of Culicoides brevitarsis in transmitting and spreading the virus has been characterized in detail [7], [8]. Incidence of AKAV in field collected Culicoides has also been studied in Israel [9], [10], the Oman [11] and the Republic of South Africa [12], where the major Afro-tropical arbovirus vector Culicoides imicola is believed to play a primary role in transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Vector competence studies for these arboviruses are most complete for AKAV, particularly in Australia where the role of Culicoides brevitarsis in transmitting and spreading the virus has been characterized in detail [7], [8]. Incidence of AKAV in field collected Culicoides has also been studied in Israel [9], [10], the Oman [11] and the Republic of South Africa [12], where the major Afro-tropical arbovirus vector Culicoides imicola is believed to play a primary role in transmission.…”
Section: Introductionmentioning
confidence: 99%
“…This means that midges of C. schultzei complex act as one of the BTV vectors, at least, in the state of West Bengal. Other workers have reported the presence of BTV in various species of Culicoides from different countries [4,[26][27][28]. Earlier, BTV was isolated from pooled sample of Culicoides midges, collected from the western part of India [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of C. imicola to a variety of strains of BTV, including an isolate of BTV-9 from Kosovo in Europe (Venter et al, 2005), has been demonstrated in the laboratory (Venter et al, 1991(Venter et al, , 1998(Venter et al, , 2006aPaweska et al, 2002). These laboratory results are supported by numerous, geographically localized, field isolations of BTV (including BTV-8), from field-collected C. imicola (Walker & Davies, 1971;Braverman et al, 1981;Mellor et al, 1984;Blackburn et al, 1985;Braverman et al, 1985;Nevill et al, 1992b;Barnard et al, 1998;Venter et al, 2006b). Susceptibility studies involving the historical reference strains of various BTV serotypes and field-collected, livestock-associated Culicoides species indicate significant differences according to the isolate used.…”
Section: Introductionmentioning
confidence: 92%